1994
DOI: 10.1017/s0022215100126453
|View full text |Cite
|
Sign up to set email alerts
|

An open safety pin in the larynx: a case report

Abstract: Inhalation of a foreign body is a serious event. The number of foreign bodies that become impacted in the larynx is small and requires urgent recognition. We describe the case of a six-month-old baby with an impacted open safety pin in the larynx. The sharp end of the safety pin was upwards and had penetrated the anterior end of the left vocal fold. We discuss the management and describe our method of removal of the foreign body. Tracheostomy was not required in this case and the child had an uneventful recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
0
4
0
1
Order By: Relevance
“…6 cuffed portex tube, under direct vision of rigid endoscope under general anesthesia. Hussain et al 9 reported a case of a 6-month-old infant with an impacted open safety pin in the larynx with the sharp end penetrating the anterior end of left vocal cord. They did not do a tracheostomy for removal of the foreign body.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…6 cuffed portex tube, under direct vision of rigid endoscope under general anesthesia. Hussain et al 9 reported a case of a 6-month-old infant with an impacted open safety pin in the larynx with the sharp end penetrating the anterior end of left vocal cord. They did not do a tracheostomy for removal of the foreign body.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…Hussain et al (1994) [5] reported a case of open safety pin in the larynx in a 6 month old boy, which was retrieved under inhalation anesthesia without intubation/tracheostomy. They have suggested that use of a suction tube into which the sharp end of the safety pin could be inserted prior to being brought out as a useful method.…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal foreign bodies are not always lethal 2–4,13-15 . Nonetheless, the largest recent review of laryngeal foreign bodies revealed the potential for grave consequences in patients with true glottic foreign bodies 13 .…”
Section: Discussionmentioning
confidence: 99%
“…He removed two laryngeal foreign bodies with the aid of a gaseous anesthetic, halothane, whereas the patient maintained spontaneous respirations. Hussain et al 15 removed a nonobstructing safety pin from the larynx after inducing anesthesia with halothane and nitrous oxide. Anesthesia was maintained with propofol and atracurium while jet ventilation continued oxygenation.…”
Section: Discussionmentioning
confidence: 99%